Profile of Science Generic Skills in Biology Learning Materials for Students in Class X - Muhammad Zainal Abidin; Nurul Hidayati Utami (FKIP ULM, 2023)
Generic Science Skills (GSS) are the ability to think and act based on the knowledge possessed by individuals. Every human being has generic science skills that need to be developed along with the development of the human brain. This is because generic science skills can be developed in accordance with the development of the level of human thinking. After the COVID-19 pandemic, teaching and learning activities experienced changes in the learning process. This resulted in learning originally carried out in the network (online) turning into offline learning (offline). Biology is a science that allows students to discover for themselves the concepts and facts contained in the biology material. Finding concepts in biology requires direct observation of biological objects. This study aimed to describe generic science skills among class X students at SMAN 1 Daha Utara. The research was conducted using a descriptive method. The description of students' generic science skills was obtained from filling out the questionnaire distributed to students. The generic science skills questionnaire used uses aspects that refer to Brotosiswoyo in 2001, which contain direct observation, indirect observation, awareness of scales, symbolic language, a framework of mind obeying the principles of natural law, logical inference, the law of cause and effect, mathematical modeling, and building the concept. This study took the population of all class X students of SMAN 1 Daha Utara. The sample for this study took 98 students randomly from six classes, namely classes X1-X6. This study uses data analysis techniques that are carried out by categorizing test results based on low, medium, and high categories. Based on the results of this study, it appears that students' generic science skills are included in the high category.